Identification of genes related to drought in native potatoes using RNA-Seq - Torres, Yerisf (2013)
The recent advent RNA sequencing technology (RNA-Seq), a massively parallel sequencing method for transcriptome analysis, provides an opportunity to understand the expression profile of plants in response to biotic and abiotic stress. In this study, the mRNA was sequencing from leaves and roots of two native potato varieties at different levels of drought. Fifty-base-pair reads from whole mRNAs were mapped to the potato genomic sequence: 75 – 82% mapped uniquely to the genome, 6 – 14% mapped to several locations in the genome and 9 – 12% had no match in the genome. Comparing expression profiles, 887 to 1925 genes were found to be induced/repressed by drought in the sensible variety and 998 to 1995 in the tolerant. This research provides valuable information for future studies and deeper understanding of the molecular mechanism of drought resistance in potato and related species.